DEVELOPMENT OF TEACHING MATERIALS TO IMPROVE THE UNDERSTANDING OF MATERIALS IN THE COMPUTER APPLICATIONS COURSE OF PGSD STUDENTS OF WIJAYA KUSUMA UNIVERSITY SURABAYA - Noviana Desiningrum; Savitri Suryandari (RADJA PUBLIKA, 2025)
This research was conducted because students felt that the existing teaching materials were boring, less interesting, and less able to make students understand the material easily. Teaching materials that can make it easier for students to understand the material are teaching materials that are made by themselves between students and lecturers, so that they do not only buy books at publishers, but students can be directly involved in writing the material. The computer application teaching materials themselves have never been made by lecturers before. So it is necessary to develop teaching materials in computer application courses so that students can more easily and understand the material. The purpose of this study is to describe the procedure for developing teaching materials, producing appropriate teaching materials, and describing the effectiveness of developing teaching materials. The type of research is Research & Development (R & D). The results of the research that has been conducted, it is known that the computer application teaching materials have been validated by media expert lecturers and learning material experts. Based on the validation results from media experts, an average of 36.00 was obtained, which is included in the